2022
DOI: 10.1177/15248380221082088
|View full text |Cite
|
Sign up to set email alerts
|

Non-Partner Sexual Violence Among Asian American, Native Hawaiian, and Pacific Islander Adults: A Scoping Review

Abstract: The Asian American, Native Hawaiian, and Pacific Islander (AANHPI) population is rapidly growing in the United States. Despite sexual violence being a persistent and significant public health issue, research on this topic among AANHPIs is lacking. The study objective is to conduct a systematic scoping review on the published literature on non-partner sexual violence among AANHPIs to identify gaps and priorities to inform actionable research. The systematic review was conducted following the PRISMA Protocol for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Finally, nearly two in five survivors report suicidal ideation and attempts, and medium to large effect sizes are found when comparing suicidality between survivors and controls (Ullman, 2004 ; Chen et al, 2010 ; Peterson et al, 2011 ; Dillon et al, 2013 ; Ba and Bhopal, 2017 ; Dworkin et al, 2017 ; Klein et al, 2022 ; Nicholas et al, 2022 ; Spencer et al, 2023 ). However, differences in depression and suicidal ideation between survivors and controls are not consistently confirmed in some reviews (Ullman, 2004 ; Ribeiro et al, 2009 ; Beydoun et al, 2012 ; Dillon et al, 2013 ; Finneran and Stephenson, 2013 ; Wadsworth and Records, 2013 ; Sparrow et al, 2017 ; Paulson, 2020 ; Forkus et al, 2021 ; Lim et al, 2022 ; Lombardi et al, 2023 ). Survivors also report feeling increased anger according to some reviews (Godier-McBard and Jones, 2020 ; Kahsay et al, 2020 ; Klein and Martin, 2021 ; Rani et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, nearly two in five survivors report suicidal ideation and attempts, and medium to large effect sizes are found when comparing suicidality between survivors and controls (Ullman, 2004 ; Chen et al, 2010 ; Peterson et al, 2011 ; Dillon et al, 2013 ; Ba and Bhopal, 2017 ; Dworkin et al, 2017 ; Klein et al, 2022 ; Nicholas et al, 2022 ; Spencer et al, 2023 ). However, differences in depression and suicidal ideation between survivors and controls are not consistently confirmed in some reviews (Ullman, 2004 ; Ribeiro et al, 2009 ; Beydoun et al, 2012 ; Dillon et al, 2013 ; Finneran and Stephenson, 2013 ; Wadsworth and Records, 2013 ; Sparrow et al, 2017 ; Paulson, 2020 ; Forkus et al, 2021 ; Lim et al, 2022 ; Lombardi et al, 2023 ). Survivors also report feeling increased anger according to some reviews (Godier-McBard and Jones, 2020 ; Kahsay et al, 2020 ; Klein and Martin, 2021 ; Rani et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, reviews show that a quarter to more than three-quarter of survivors report experiencing PTSD-related symptoms. Reviews including primary studies with control groups of non-survivors or survivors of other types of trauma report medium to large effect size differences in PTSD symptoms between groups (Van Berlo and Ensink, 2000 ; Classen et al, 2005 ; Wilness et al, 2007 ; Cook et al, 2011 ; Peterson et al, 2011 ; Steine et al, 2012 ; Trevillion et al, 2012 ; Wadsworth and Records, 2013 ; Ba and Bhopal, 2017 ; Chmielowska and Fuhr, 2017 ; Dworkin et al, 2017 , 2023 ; Sparrow et al, 2017 ; Bows, 2018 ; Dworkin, 2018 ; Dame et al, 2020 ; Kahsay et al, 2020 ; Alessi et al, 2021 ; Forkus et al, 2021 ; Gallegos et al, 2021 ; Klein and Martin, 2021 ; Mazza et al, 2021 ; Zarchev et al, 2021 ; Klein et al, 2022 ; Lim et al, 2022 ; Spencer et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further research is needed to disaggregate data and better understand rates of USCV among AIAN and NHPI student subgroups, including Southeast Asian populations, and to consider how experiences of racism intersect with sexual violence victimization. 13 Additionally, further research should focus on the speci c experiences of Black sexual and gender minority students and the compounding impacts of anti-Blackness, racial fetishization, transphobia, and homophobia on sexual violence victimization. 14,15 Scholars have argued that Black LGBTQ + students may be at greater risk for sexual assault due to racist and hypersexualized school climates, which reinforce racist stereotypes around Black student sexualities while further perpetuating homophobia.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, Asian Americans are severely under-researched; a recent portfolio review of clinical research funded by the National Institutes of Health (NIH) found that Asian American, Native Hawaiian, and Pacific Islander participants composed 0.17% of the total NIH budget over 26 years (Ethoan et al, 2019). A recent systematic scoping review on non-partner sexual violence among Asian Americans similarly noted the lack of data both in the overall Asian American population as well as among disaggregated data among Asian American sub-groups (Lim et al, 2022).…”
mentioning
confidence: 99%